„Tylko zdechlaki nie lubią żuru”. Studium męskiej przemocy w „Gnoju” Wojciecha Kuczoka - Górecki, Przemysław (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article offers an analysis of Wojciech Kuczok’s renowned novel Gnój (Muck) from the perspective of studies on masculinity. It focuses on how hegemonic masculinity (a term popularized by the Australian researcher Raewyn Connell), represented in the novel by the protagonist’s father, functions, and on the forms of expressing a type of masculinity that the father does not accept, namely weakness, lameness and no aptitude for hypermasculinity, depicted in the protagonist. The article also analyses the narration and building the linguistic image of the world presented in the novel, the main manner of expressing masculinity by the father and the way he reinforces his hegemonic status.